Urban Cultural Space in the Context of Evolutionism - Freidlina, Viktoriia; Uvarova, Tetiana (Journal of History Culture and Art Research, 2020)
Attempts to determine the essence of urban culture were made in the framework of different approaches: civilizational, philosophical, anthropological, sociological, and others. This article is concerned with the analysis of the urban cultural space phenomenon from the evolutionary point of view. Originating as the first ethnographic theory in the works of German historian Friedrich Gustav Klemm, cultural evolutionism was further developed in the evolutionary theory of cultural development, the founder of which is the English ethnologist Edward Burnett Tylor. The problems of the evolutionary theory of culture were widely discussed in scientific circles and found common ground with such ideas as the “axial age” concept by Karl Jaspers and the doctrine of the noosphere. Some common points in understanding the synergistic mechanisms of cultural activities can be found in the holistic "philosophy of integrity". An evolutionary analysis of urban cultural space remains relevant today. In this article, we analyze the possibility of studying the processes of cultural transformation in the context of changes in the forms of joint social life, developing from the incoherent homogeneous structure of ancient human settlements to the complex heterogeneous structure of modern highly urbanized urban communities. Also, we attempted to justify the advisability of applying the evolutionary approach to the analysis of the laws of formation, development and improvement of the cultural space of modern cities.